The impact of methamphetamine on psychosocial variables in patients from Iraq - Abbass, Marwah; Al-Hemiary, Nesif; Sahib, Hayder B. (Frontiers in Psychiatry, 2024)
1) Background: The current work reviews the psychosocial factors associated with different urinary methamphetamine concentration levels. (2) Methods: From April to November 2023, 243participants from Baghdad's Al-Ataa Hospital will be the subject of a cross-sectional descriptive analysis study. We included 73 patients in this study. (3) Results: Urinary methamphetamine concentration levels were from 3 ng/ml to 92274 ng/ml, with a mean ±SD of 10873.6 ±18641.Patients diagnosed with (MDD) exhibited higher scores on GHQ-30, UCLA, MOAS, and BDI-II with a significant P-value of 0.0001,0.001, 0.0001, and 0.0001 consequently with an effect size of 0.015, 0.001, 1.05, and 3.24 respectively. (4) Conclusions: The multi-screening test can produce a false positive. It frequently interferes with other drugs, especially antidepressants. This will result in patients being stigmatized and accused. On the other hand, those who accidentally come into contact with crystal smoke will experience the same withdrawal symptoms as addicted patients.Their urinary methamphetamine level (titer) could have negative results. Urinary methamphetamine levels should be zero in healthy patients. In this situation, screening tests, expert opinion, and urine methamphetamine testing are strongly recommended.